Identification of Dominant Fungal Species on Stored Rice Grains by Morphological Characteristics and Multigene Analysis - QI Zhi-hui; ZHANG Hai-yang; TIAN Lin; ZHUANG Yuan; LI Bing; TANG Fang (Liang you shipin ke-ji, 2022)
The growth of fungi on rice grains during storage will affect rice quality. In severe cases, these fungi will produce mycotoxins and cause food safety issues. It is the premise of effective prevention and control of deleterious fungi to determine the fungal community composition of rice grains during storage and accurately identify the dominant species, which is of great significance in ensuring the quality safety and food safety of rice grains. In this study, we used the methods of traditional microbial separation culture to investigate the fungal communities of stored rice grains from warehouses of different regions. In combination with the sequence of ex-types and authentic strains, we used morphological observations and multigene phylogenetic analysis to accurately identify the dominant fungal species of stored rice grains in China. The dominant species were A. flavus, A. niger and A. montevidensis (A. amstelodami) in Southern China and A. proliferans and A. montevidensis in Northern China. The detailed identification process and related data of the predominant fungal species on the stored rice grains in the North and South China were expounded in this paper, which has provided a reference for the accurate identification of deleterious fungi in grains.